(untitled) (Ustozlar uchun, 2025)
Antibiotic resistance poses a significant threat to global public health, driven by the emergence of novel bacterial phenotypes capable of evading conventional therapies. This article explores methods for identifying and analyzing antibiotic-resistant bacteria, including genomic sequencing, phenotypic assays, and bioinformatics approaches. The study reviews mechanisms of resistance such as horizontal gene transfer, efflux pumps, and enzymatic inactivation. By examining recent outbreaks and resistant strains, the research emphasizes the importance of rapid detection, continuous surveillance, and development of innovative therapeutic strategies to combat antimicrobial resistance.¹